Cochlear implantation in children with meningitis related deafness: The influence of electrode impedance and implant charge on auditory performance – A case control study. (October 2018) - Helmstaedter, Victor; Buechner, Andreas; Stolle, Stefan; Goetz, Friedrich; Lenarz, Thomas; Durisin, Martin
Abstract: Objectives: Bacterial meningitis can cause a labyrinthitis. Consequences often are intracochlear soft tissue neoformation (cochlear obliteration) or intracochlear osteoneogenesis (cochlear ossification) and deafness. Cochlear implantation becomes challenging and hearing rehabilitation is complicated. This retrospective case-control-study aimed to find correlations between morphologic, electric and functional parameters. Methods: The study group included children, who lost hearing due to a bacterial meningitis (n = 35 cases). Using preoperative computed tomography and intraoperative findings we grouped into 'unaltered cochleae', 'obliterated cochleae' and 'ossified cochleae'. Control group children suffered from deafness (n = 16) of other aetiology and presented with radiologically unchanged cochleae. Postoperative routine controls documented impedances, stimulation charge and hearing tests a various time points, which all were analysed. Results: Control group patients showed a mean impedance of 6.3 kΩ and the mean charge applied was 19 nC. The study group averaged at 7.9 kΩ and 24.6 nC respectively. Patients with ossified cochleae had increased values of 8.6 kΩ and 29.7 nC. The control group reached a monosyllabic word understanding of 74% and the study group of 58%. Patients with ossified cochleae reached 36%. Conclusions: Impedances and stimulation charge influence each other. Increased charge is necessary for higher cochlear implant output. Despite higher charges, patients with obliterated and patients with ossified cochleae significantly perform worse in hearing rehabilitation. Reduced audiological outcome in study group patients without morphologic cochlear changes furthermore hints at additional factors besides cochlear tissue neogenesis like postinflammational changes at the neural pathway.